Disorders of Consciousness Associated With COVID-19: A Prospective Multimodal Study of Recovery and Brain Connectivity. (18th January 2022) - Fischer, David; Snider, Samuel B.; Barra, Megan E.; Sanders, William R.; Rapalino, Otto; Schaefer, Pamela; Foulkes, Andrea S.; Bodien, Yelena G.; Edlow, Brian L.
Abstract : Background and Objectives: In patients with severe coronavirus disease 2019 (COVID-19), disorders of consciousness (DoC) have emerged as a serious complication. The prognosis and pathophysiology of COVID-DoC remain unclear, complicating decisions about continuing life-sustaining treatment. We describe the natural history of COVID-DoC and investigate its associated brain connectivity profile. Methods: In a prospective longitudinal study, we screened consecutive patients with COVID-19 at our institution. We enrolled critically ill adult patients with a DoC unexplained by sedation or structural brain injury and who were planned to undergo a brain MRI. We performed resting-state fMRI and diffusion MRI to evaluate functional and structural connectivity compared to healthy controls and patients with DoC resulting from severe traumatic brain injury (TBI). We assessed the recovery of consciousness (command following) and functional outcomes (Glasgow Outcome Scale Extended [GOSE] and the Disability Rating Scale [DRS]) at hospital discharge and 3 and 6 months after discharge. We also explored whether clinical variables were associated with recovery from COVID-DoC. Results: After screening 1, 105 patients with COVID-19, we enrolled 12 with COVID-DoC. The median age was 63.5 years (interquartile range 55–76.3 years). After the exclusion of 1 patient who died shortly after enrollment, all of the remaining 11 patients recovered consciousness 0 to 25 days (median 7 [5–14.5] days) after the cessation of continuous IV sedation. At discharge, all surviving patients remained dependent: median GOSE score 3 (1–3) and median DRS score 23 (16–30). Ultimately, however, except for 2 patients with severe polyneuropathy, all returned home with normal cognition and minimal disability: at 3 months, median GOSE score 3 (3–3) and median DRS score 7 (5–13); at 6 months, median GOSE score 4 (4–5), median DRS score 3 (3–5). Ten patients with COVID-DoC underwent advanced neuroimaging; functional and structural brain connectivity in those with COVID-DoC was diminished compared to healthy controls, and structural connectivity was comparable to that in patients with severe TBI. Discussion: Patients who survived invariably recovered consciousness after COVID-DoC. Although disability was common after hospitalization, functional status improved over the ensuing months. While future research is necessary, these prospective findings inform the prognosis and pathophysiology of COVID-DoC. Trial Registration Information: ClinicalTrials.gov identifier: NCT04476589.